Analysis of Intestinal Short-Chain Fatty Acid Metabolism Profile After Probiotics and GLP-1 Treatment for Type 2 Diabetes Mellitus - Min, Qiuxia; Wang, Yan; Jin, TaiCheng; Zhu, Lei; Wu, XianYan; Li, YiKun; Wang, YanJiao; Xu, Ning (Frontiers in Endocrinology, 2022)
Type 2 diabetes accounts for about 90% of diabetes patients, and the incidence of diabetes is on the rise as people's lifestyles change. Compared with GLP-1 treatment, probiotic treatment can directly regulate homeostasis of the host gut microbe, and thus homeostasis of its metabolites. Currently, the regulatory role of probiotics on intestinal metabolites after treatment of type 2 diabetes mellitus remains unclear. The purpose of this study was to investigate the therapeutic effect of probiotics on type 2 diabetes mellitus and its regulatory effect on short-chain fatty acids, which are metabolites of intestinal microorganisms. I collected feces from 15 patients with diabetes before treatment and 15 patients with type 2 diabetes after treatment with GLP-1 and probiotics. The abundance of short-chain fatty acids in feces was determined by GC-MS. Results Both GLP-1 and probiotics could improve the levels of blood glucose, urine glucose and BMI in patients with type 2 diabetes. After glP-1 treatment, two short-chain fatty acids (butyric acid and valerate acid) in intestine were significantly changed. Propionic acid and isovalerate were significantly changed after probiotic treatment. At the same time, keGG signal pathway enrichment results showed that probiotics intervention mainly achieved the purpose of treating type 2 diabetes through regulating protein and carbohydrate metabolism. Taken together, our study shows changes in intestinal short-chain fatty acids after probiotics or GLP-1 treatment of type 2 diabetes, which will provide us with new insights into the mechanism of probiotics treatment of type 2 diabetes, as well as potential intervention targets for diabetes treatment.